Modelling, simulation and validation for a multimode double-pendulum overhead crane - Jaafar, Hazriq Izzuan; Syed Hussien, Sharifah Yuslinda; Ghazali, Rozaimi; Md Ghazaly, Mariam; Azizat Johari, Mohd Khairul; Ramli, Liyana (ARQII Publication, 2024)
This paper focuses on the modelling of a multimode double-pendulum overhead crane (MDPOC) system which generates double-pendulum phenomenon. The MDPOC is far more complex than those of single-pendulum overhead cranes due to the additional degree of freedom, greater nonlinearities, and stronger internal couplings especially involving two or more oscillation frequencies with multimode dynamic effects. More interestingly, two scenarios under fixed and varying cable lengths (payload hoisting) are considered which are closer to the real practical crane. The dynamic crane models are derived using Lagrange’s method. Simulations using the Matlab/Simulink block diagram, as well as experiments on a laboratory overhead crane are used to verify and validate the accuracy of MDPOC mathematical modelling. The simulation and experimental results demonstrate the superiority and similar pattern of the trolley position, hook oscillation and payload oscillation under fixed and varying cable lengths that verified the mathematical modelling of MDPOC. It is beneficial for crane operators to understand the dynamic model of MDPOC and useful for future analysis of controller implementation with confidence by researchers.